MicroRNAs modulated by local mIGF-1 expression in mdx dystrophic mice - Pelosi, Laura; Coggi, Angela; Forcina, Laura; Musarò, Antonio (Frontiers in Aging Neuroscience, 2015)
Duchenne muscular dystrophy (DMD) is a X-linked genetic disease in which the absence of dystrophin leads to progressive lethal skeletal muscle degeneration. It has been demonstrated that among genes which are important for proper muscle development and function, micro-RNAs (miRNAs) play a crucial role. Moreover, altered levels of miRNAs were found in several muscular disorders, including DMD. A specific group of miRNAs, whose expression depends on dystrophin levels and whose deregulation explains several DMD pathogenetic traits, has been identified. Here, we addressed whether the anabolic activity of mIGF-1 on dystrophic muscle is associated with modulation of microRNAs expression. We demonstrated that some microRNAs are strictly linked to the dystrophin expression and are not modulated by mIGF-1 expression. In contrast, local expression of mIGF-1 promotes the modulation of other microRNAs, such as miR-206 and mir-24, along with the modulation of muscle specific genes, which are associated with maturation of regenerating fibers and with the stabilization of the differentiated muscle phenotype. These data suggest that mIGF-1, modifying the expression of some of the active players of muscle homeostasis, is able, even in absence of dystrophin expression, to activate circuitries that confer robustness to dystrophic muscle.